2023
DOI: 10.2147/prbm.s414623
|View full text |Cite
|
Sign up to set email alerts
|

Research on Employee Voice Intention: Conceptualization, Scale Development, and Validation Among Enterprises in China

Abstract: Expressing opinions and ideas in the workplace is an important aspect of organizational development and employee wellbeing. However, employee voice intention, which refers to an employee's willingness to share their opinions or ideas, is an area that has received limited attention in research. Therefore, the aim of this study was to develop and validate a reliable measurement tool for employee voice intention. Methods: The study followed a three-stage process. First, in-depth interviews were conducted with man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…As is shown in Table 8 , the results revealed that the “emotional exhaustion” dimension was 0.94, while that of the “depersonalization” dimension was 0.82, and the overall Cronbach’s α coefficient of the scale was 0.92. Both the reliability coefficient and the reliability coefficient of each dimension exceeded the stand of 0.70, which indicated that the social burnout scale developed in this study had good reliability ( Ouyang et al, 2023 ).…”
Section: Resultsmentioning
confidence: 67%
“…As is shown in Table 8 , the results revealed that the “emotional exhaustion” dimension was 0.94, while that of the “depersonalization” dimension was 0.82, and the overall Cronbach’s α coefficient of the scale was 0.92. Both the reliability coefficient and the reliability coefficient of each dimension exceeded the stand of 0.70, which indicated that the social burnout scale developed in this study had good reliability ( Ouyang et al, 2023 ).…”
Section: Resultsmentioning
confidence: 67%